2002
DOI: 10.1128/iai.70.4.1842-1852.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Cytochrome c Maturation Locus of Legionella pneumophila Promotes Iron Assimilation and Intracellular Infection and Contains a Strain-Specific Insertion Sequence Element

Abstract: Previously, we obtained a Legionella pneumophila mutant, NU208, that is hypersensitive to iron chelators when grown on standard Legionella media. Here, we demonstrate that NU208 is also impaired for growth in media that simply lack their iron supplement. The mutant was not, however, impaired for the production of legiobactin, the only known L. pneumophila siderophore. Importantly, NU208 was also highly defective for intracellular growth in human U937 cell macrophages and Hartmannella and Acanthamoeba amoebae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(90 citation statements)
references
References 86 publications
(74 reference statements)
4
82
4
Order By: Relevance
“…Although FrgA is homologous with hydroxamate synthetases and frgA promotes growth within the iron-limited intracellular niche in macrophages (35), frgA mutants proved not to be defective for CAS reactivity when grown in low-iron CDM (39). We also observed that the cytochrome c maturation operon, which promotes L. pneumophila growth in low-iron media as well as siderophore expression in several other types of bacteria, is not required for legiobactin production (47,82). In another recent study, the feoB ferrous iron transporter showed no role in the generation of L. pneumophila CAS reactivity (63).…”
mentioning
confidence: 58%
“…Although FrgA is homologous with hydroxamate synthetases and frgA promotes growth within the iron-limited intracellular niche in macrophages (35), frgA mutants proved not to be defective for CAS reactivity when grown in low-iron CDM (39). We also observed that the cytochrome c maturation operon, which promotes L. pneumophila growth in low-iron media as well as siderophore expression in several other types of bacteria, is not required for legiobactin production (47,82). In another recent study, the feoB ferrous iron transporter showed no role in the generation of L. pneumophila CAS reactivity (63).…”
mentioning
confidence: 58%
“…Additionally, in some prokaryotes, a defect in the biogenesis of cytochrome c leads to a dramatic increase in synthesis and excretion of heme biosynthetic intermediates (10,21). Other reported phenotypes of cytochrome c mutants are loss of copper resistance (51) and pyoverdine production (19) in Pseudomonas fluorescens, defects in nitrogen fixation in B. japonicum and R. phaseoli (36,43), and reduced intracellular infection in Legionella pneumophila (50), as well as defects in high-affinity iron acquisition in Rhizobium leguminosarum and P. fluorescens (9,52). However, there are no reports describing the relationship between IAA production and cytochrome c in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Because heme biosynthesis depends on central metabolism (e.g., glutamate or succinyl coenzyme A and glycine), a limiting factor for heme biosynthesis is often the free iron levels (27,42,56). Based on the presence of the "heme reservoir" CcmE (24) and the fivefold-higher affinity for heme, we speculate that organisms in which heme synthesis is limited, such as organisms faced with low-iron environments, would have an advantage using system I.…”
Section: Discussionmentioning
confidence: 99%